(untitled) - Wagner, Barbara (New York, 2002)
Tho book will help you: Choose the investments that fit into your college savings plan–stocks, bonds, mutual funds, CollegeSure CDs, and U.S. Treasury Bills; Use educational savings provisions in the Economic Growth and Tax Relief Reconciliation Act of 2001 to speed up the growth of your college savings Understand how 529 savings plans stack up to prepaid plans, Education IRAs, UGMAs, and UTMAs; Select a financial planner who will help you plot a strategy for college savings; Apply for financial aid such as grants, loans, work-study jobs, and scholarships
Keywords: College costs,Finance, Personal,Hỗ trợ sinh viên; United States,United States